Fostering Water Resilience in Brazil Turning Strategy into Action (OECD Studies on Water, 2022)
Brazil made significant progress in managing water resources since the adoption of the National Water Law in 1997 and the creation of the National Water and Sanitation Agency (ANA) in 2000. Nevertheless, water security challenges persist and will be aggravated by megatrends such as climate change, population growth, urbanisation, and the economic, social and environmental consequences of the COVID-19 pandemic. The report calls for a modern approach to water security, balancing supply and demand management, grey and green infrastructure, and risk management and resilience while embracing a holistic view that connects water to other strategic areas such as environment, land use and territorial development. The report builds on a decade of policy dialogue between the OECD and the National Water and Sanitation Agency (ANA) of Brazil. It provides an action plan to support the country to: (1) shift from a risk-based approach to a resilience approach to understand vulnerabilities and minimise the duration and magnitude of failures; (2) make river basin organisations deliver and use economic instruments to tackle water risks; and (3) accompany infrastructure development with regulatory oversight and monitoring